HUBUNGAN INFORMASI PELAPORAN EARNINGS AKUNTANSI TERHADAP PERGERAKAN RETURNS SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK JAKARTA - Rosna K. Haraharap; Arga Fitria (Media Riset Akuntansi, Auditing & Informasi, 2008)
The purpose of this research is to know whether the negative earnings stock have lower sensitivity level or lower Earnings Response Coefficient (ERC) to stock return than the positive earnings stock and this research also aim to know whetherthe negative earnings stock will have weaker level strength of correlation (R2) to stock return than the positive earnings stock. The samples are 25 fisted manufactured company at Jakarta Stock Exchange during 2000-2004 which selected using purposive non random sampling. Data analyze method used is linier regression. The result of this research is that the negative earnings stock will have the lower level sensitivity or lower Earnings Response Coefficient (ERC) to stock return, compared to the level sensitivity (ERC) of positive earnings stock This research also finds that the negative earnings stock will have weaker level strength of correlation (R2) to stock return, compared to the level strength of correlation (R2) of positive earnings stock.Keywords: Negative earnings, Positive earnings, Stock return, Earnings response coefficient, Return-earnings association